Twitter Use among Academic Urology Programs. Issue 3 (May 2017) - Farber, Nicholas J.; Koprowski, Christopher J.; Modi, Parth K.; Wang, Wei; Dubin, Justin M.; Kwon, Young Suk; Elsamra, Sammy E.
Abstract : Introduction: : Twitter is a popular social media platform that has an important role in the urological community. Benefits include dissemination of knowledge, cross‐institutional communication, amplification of conference content and greater engagement of the public, with increased departmental exposure. However, to date the use of Twitter by academic urology programs has yet to be examined. Methods: : The existence and profile of institutional Twitter accounts of each United States urology residency program was recorded and reassessed in 6 months. Geographic stratification of Twitter presence was evaluated with chi‐square analysis. The relationship between Twitter variables and U.S. News and World Report ranking was evaluated using Pearson's correlation coefficient. Detailed account data were collected for the top 5 accounts by tweet volume. Conference hashtag activity for the 2013 to 2015 AUA (American Urological Association) annual meetings was compared. Results: : The total number of residency programs with a Twitter account is 38 (30%). Median number of tweets, followers, following and age of account was 58, 154, 107.5 and 20 months, respectively. Geographic stratification failed to show significant difference (p=0.73). Of the 38 accounts 11 were inactive over 6 months. The 27 active accounts had an average percent increase of 161% in tweets and 148% in followers. Twitter presence showed no difference in U.S. News and World Report ranking (p=0.51). The conference hashtags #AUA13 to #AUA15 increased in activity each year. Conclusions: : A minority of academic urology programs use Twitter. Account activity grew significantly with time. The role of Twitter is still being defined but is rapidly gaining traction as a new powerful communication tool among urologists and with the public.